Global human trafficking : critical issues and contexts - Dragiewicz, Molly (Abingdon, Oxon : Routledge, 2015)
'Human trafficking has moved from relative obscurity to a major area of research, policy and teaching over the past ten years. Research has sprung from criminology, public policy, women's and gender studies, sociology, anthropology, and law, but has been somewhat hindered by the failure of scholars to engage beyond their own disciplines and favoured methodologies. Recent research has begun to improve efforts to understand the causes of the problem, the experiences of victims, policy efforts, and their consequences in specific cultural and historical contexts. Global Human Trafficking: Critical issues and contexts foregrounds recent empirical work on human trafficking from an interdisciplinary, critical perspective. The collection includes classroom-friendly features, such as introductory chapters that provide essential background for understanding the trafficking literature, textboxes explaining key concepts, discussion questions for each chapter, and lists of additional resources, including films, websites, and additional readings for each chapter. The authors include both eminent and emerging scholars from around the world, drawn from law, anthropology, criminology, sociology, cultural studies, and political science and the book will be useful for undergraduate and graduate courses in these areas, as well as for scholars interested in trafficking'--
Includes bibliographical references and index.
Keywords: Human trafficking